Uang Elektronik (E-Money) dalam Perspektif Maqashid Syariah - Muhammad Ihsan H.M. Baso; Achmad Abubakar; Halimah Basri (el-Jizya: Jurnal Ekonomi Islam, 2023)
Electronic money is one of the payment tools in electronic form where the value of money is stored in certain electronic media, the user or users must first deposit the funds to the issuer or issuer, then stored in electronic media in the form of an e-money before using it for transaction purposes. at merchants that provide payment facilities using electronic money. The purpose of this study is to analyze e-money from the perspective of the Koran and to discuss the contracts contained in all transactions through e-money. The method used in this study is a qualitative method, with a library research approach,namely a series of activities related to library data collection methods, reading and recording and processing research materials from supporting literature. Today's e-money has been transformed in the development of world technology and among the halal community and has fulfilled the rules of the quran and sharia maqasid as a transaction tool. Researchers want to review E-money from the perspective of the quran, whether it is in accordance with the principles of the quran and the contracts contained in e-money